2016
DOI: 10.2139/ssrn.2839761
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Costs of Government Surveillance: Insights from Stasi Spying in East Germany

Abstract: Despite the prevalence of government surveillance systems around the world, causal evidence on their social and economic consequences is lacking. Using county-level variation in the number of Stasi informers within Socialist East Germany during the 1980s and accounting for potential endogeneity, we show that more intense regional surveillance led to lower levels of trust and reduced social activity in post-reunification Germany. We also find substantial and long-lasting economic effects of Stasi spying, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…Our paper contributes to several strands of research. In addition to the literature on memory, experience effects, and salience cited above, our analysis closely relates to a literature in political economy and labor economics suggests that political and labor-market experiences have long-lasting effects through different channels, such as the formation of preferences and norms, or due to frictions in post-experience adjustment (Alesina andFuchs-Schündeln (2007), Lichter, Löffler, andSiegloch (2019)). Fuchs-Schuendeln and Schuendeln (2015), for example, argue that the time a person has lived under a democratic system determines her political preferences for democracy.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our paper contributes to several strands of research. In addition to the literature on memory, experience effects, and salience cited above, our analysis closely relates to a literature in political economy and labor economics suggests that political and labor-market experiences have long-lasting effects through different channels, such as the formation of preferences and norms, or due to frictions in post-experience adjustment (Alesina andFuchs-Schündeln (2007), Lichter, Löffler, andSiegloch (2019)). Fuchs-Schuendeln and Schuendeln (2015), for example, argue that the time a person has lived under a democratic system determines her political preferences for democracy.…”
Section: Introductionmentioning
confidence: 91%
“…Naturally, it is possible that this proxy is also correlated with negative experiences (for those who were policed). Lichter, Löffler, and Siegloch (2019) show, for example, that a higher spy density has negative long-term effects on trust, political participation and, ultimately, economic performance (income). The prediction is thus less clear ex ante.…”
Section: Emotional Tagging Of Communist Experiencementioning
confidence: 99%
“…see Becker et al, 2020), our study focuses on differences within the GDR. It thereby contributes to a growing literature that is concerned with intra-GDR differences (see, among others, Lichter et al, 2021;Friehe et al, 2018;Friehe and Pannenberg, 2020;Bursztyn and Cantoni, 2016) by showing that the extent to which individuals were involved in the socialist system, i.e., the extent to which they expressed conformism, can also persistently shape economic and social outcomes, depending on the system they live in.…”
Section: Introductionmentioning
confidence: 82%
“…Surveillance activities may also have more insidious long-term effects than other forms of privacy violation, potentially undermining basic trust and thereby contributing to poor economic performance. Lichter, Loeffler and Siegloch (2015) analyse the effects of surveillance by the East German Ministry for State Security (Stasi) using county-level data. They show that "higher levels of Stasi surveillance led to lower levels of social capital as measured by interpersonal and institutional trust in post-reunification Germany", and that a higher spy density is associated with "lower selfemployment rates, fewer patents per capita, higher unemployment rates and larger population losses throughout the 1990s and 2000s".…”
Section: Future Researchmentioning
confidence: 99%
“…While the Helsinki researchers found that the overt negative emotions reduced over time, there was also evidence that there is a longerterm insidious effect from surveillance. A study conducted in former East Germany found that those counties that had higher levels of Stasi informers during the communist era had lower rates of economic growth and higher unemployment during the 1990s and 2000s (Lichter, Loeffler & Siegloch, 2015). The research suggests that surveillance results in individuals having lower levels of trust in institutions and other people, making it more difficult to make agreements and engage in wealth-enhancing activity.…”
Section: Introductionmentioning
confidence: 99%